Effects of follow-on therapy after denosumab discontinuation in patients with postmenopausal osteoporosis. Issue 2 (4th March 2021) - Ebina, Kosuke; Hashimoto, Jun; Kashii, Masafumi; Hirao, Makoto; Miyama, Akira; Nakaya, Hiroyuki; Tsuji, Shigeyoshi; Takahi, Koichiro; Tsuboi, Hideki; Okamura, Gensuke; Etani, Yuki; Takami, Kenji; et al.
Abstract: Objectives: To clarify the effects of follow-on therapy after denosumab (DMAb) discontinuation. Methods: In this retrospective, multicenter study, postmenopausal patients with osteoporosis who were previously treated by oral bisphosphonates (BP) ( n = 26) or teriparatide (TPTD) ( n = 27) were switched to DMAb (administered 2.6 times), and then discontinued. Patients (73.1 years, T -scores of the lumbar spine [LS] − 2.7 and femoral neck [FN] − 2.2) were switched to either (1) raloxifene (RAL) ( n = 13) or BP [(2) weekly or monthly BP (wmBP) ( n = 29) or (3) zoledronate (ZOL) ( n = 11)], based on each physician's decision (mean interval after final DMAb administration was 7.2 months). Bone mineral density (BMD) at final DMAb administration were set as baseline. Results: Changes in LS BMD at 1.5 years after final DMAb administration were −2.7% in the RAL, 0.7% in the wmBP, and 1.9% in the ZOL ( p = .31 between groups), and in FN BMD were −3.8%, −0.8%, and 1.8%, respectively ( p = .02 between the RAL and ZOL; p = .048 between the RAL and BP). Clinical vertebral fracture incidence during 1.5 years after final DMAb administration was 23.1% in the RAL, 3.4% in the wmBP, and 0.0% in the ZOL ( p = .048 between the RAL and ZOL; p = .015 between the RAL and BP). No significant differences were observed in these parameters between the wmBP and ZOL. Conclusion: These results may contribute to the selection of adequate follow-on therapy after DMAb discontinuation, although further investigations are required.